PRISTUP PISANJU KAO OBLIKOVANJU TEKSTA - Danica Pirsl; Nenad Zivanovic; Nebojsa Randjelovic (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
Within the research area of Cognitive Psychology scholars, the focus has lately been on the writing processes modelled on shaping the text. The Model of Cognitive Writing Processes by Flower and Hayes (1984) tries to explain cognitive processes and components which are included in writing a text. According to this model, text authors analyse information based on the approach similar to the one described in The Information Processing Model of Memory by Atkinson and Schiffrin (1968). The authors' analysis of the data can also be explained with The Levels of Processing Theory by Craik and Lockhart (1972). The quality of written text depends on the use of writing strategies and techniques. The key writing strategies for the quality of the written text are: strategic planning, strategy of the design elaboration, and strategy of correcting the finished text. The process of writing the text is a very complex skill. The level of cognitive effort necessary for some phases of the writing process is very high. There are many interindividual differences in the writing skill level, depending on the cognitive level of the individual, sex, age, attitudes to writing, reading skills etc. For the teaching of writing, modelled on shaping the text, a more general recommendation is the interactional or process approach.